Surgical Treatment of Submandibular Gland Pathologies - Musa Özbay (Dicle Medical Journal, 2016)
Objective: We aimed to evaluate clinical presentations, histopathological diagnosis and complications of patients operated for a submandibular gland pathology. Methods: Medical records of 34 patients who were operated for a submandibular gland pathology between 2007 and 2016 years evaluated retrospectively. Results: 21 (61.8%) of these patients were male and 13 (38.2%) were female. The mean age of the patients was 41.7±16.6 years. Post-operative histopathological diagnosis was benign in 30 patients (88.2%), malign in 4 patients (11.8%). In the benign group, diagnosis was sialoalolithiasis in 20 patients, chronic sialoadenitis in 6 patients and pleomorphic adenoma in 4 patients. In malign group, the histopathologic result for all patients was adenoid cystic carcinoma. Complication rate of submandibular excision surgery was 11.7%. Marginal mandibular nerve paresis was the most common complication. Conclusion: New surgery methods have been presented in the literature because of the incision scar and marginal mandibular nerve paresis during the transcervical surgical approach. However, submandibular gland excision through transcervical approach is still the most used and safe method.